COI metabarcoding of large benthic Foraminifera: Method validation for application in ecological studies. Issue 11 (22nd November 2022) - Girard, Elsa B.; Macher, Jan‐Niklas; Jompa, Jamaluddin; Renema, Willem
Abstract: Monitoring community composition of Foraminifera (single‐celled marine protists) provides valuable insights into environmental conditions in marine ecosystems. Despite the efficiency of environmental DNA (eDNA) and bulk‐sample DNA (bulk‐DNA) metabarcoding to assess the presence of multiple taxa, this has not been straightforward for Foraminifera partially due to the high genetic variability in widely used ribosomal markers. Here, we test the correctness in retrieving foraminiferal communities by metabarcoding of mock communities, bulk‐DNA from coral reef sediment samples, and eDNA from their associated ethanol preservative using the recently sequenced cytochrome c oxidase subunit 1 (COI) marker. To assess the detection success, we compared our results with large benthic foraminiferal communities previously reported from the same sampling sites. Results from our mock communities demonstrate that all species were detected in two mock communities and all but one in the remaining four. Technical replicates were highly similar in number of reads for each assigned ASV in both the mock communities and bulk‐DNA samples. Bulk‐DNA showed a significantly higher species richness than their associated eDNA samples, and also detected additional species to what was already reported at the specific sites. Our study confirms that metabarcoding using the foraminiferal COI marker adequately retrieves the diversity and community composition of both the mock communities and the bulk‐DNA samples. With its decreased variability compared with the commonly used nuclear 18 S rRNA, the COI marker renders bulk‐DNA metabarcoding a powerful tool to assess foraminiferal community composition under the condition that the reference database is adequate to the target taxa. Abstract : We test the correctness in retrieving foraminiferal communities by metabarcoding of mock communities, bulk‐DNA from coral reef sediment samples, and eDNA from their associated ethanol preservative using the recently sequenced cytochrome c oxidase subunit 1 (COI) marker. We compared our results to large benthic foraminiferal communities previously reported from the same sampling sites and found that bulk‐DNA metabarcoding of large benthic foraminifera showed a significantly high species richness and also detected additional species. Our study confirms that metabarcoding using the foraminiferal COI marker adequately retrieves the diversity and community composition of both the mock communities and bulk‐DNA samples.